Role Attainmetn Ibu dalam Pemberian MP – Asi dengan Peningkatan Berat Badan Bayi Usia 6-12 Bulan - Ririn Probowati; Heri Wibowo; Septi Fitrah Ningtyas; Mamik Ratnawati; Nursalam Nursalam (Jurnal Ners, 2016)
Introduction: Mother’s Role Attainment in giving additional food  will affect growth in infants. The study aims to analyze the role of mothers in the attainmet competency in giving additional food  with infant growth Age 6-12 months working area Jogoloyo Jombang Health care centre.Methods: Design used in this study was retrospectives, the population was mother of babies aged 6-12 months in Health care centre  Jombang Jogoloyo Sumobito on July 2016. Simple random sampling technique was used in this study, with sample were 130 mother. The independent variables were maternal role attainment in the competence of giving complementary feeding. The dependent variable were growth of infants aged 6-12 months. Data was collected using questionnaires and observation KIA book and analyzed using chi square with a significance level of 0.05.Results:  Results showed that ρ = 0.005 <0.05, which means that there is a relation role Attainment in giving additional food to the growth of infants aged 6-12 months.Discussion: Mother Role Attainment in giving additional food affect the babies weight. After the age of 6 months babies should receive additional food because breast milk is not sufficient nutrients to the baby's growth.